Market access and agricultural product marketing: Promoting farmer initiatives - Lothoré, Anne; Delmas, Patrick (AFD /CTA / INter-réseaux, 2009)
Farmers in sub-Saharan Africa face significant obstacles in selling their agricultural products, including unstable prices, poor infrastructure, limited market information and lack of market access. This book brings together case-studies of initiatives developed by individual farmers and farmers' organisations to improve market access, and concludes with recommendations for supporting such initiatives